Literary and Artistic Education: Social and Bellicose Conflicts - Jingxian, Yu (Pulso. Revista de educación, 2019)
Review of the book: Roig Rechou. (2017). Conflictos sociales y bélicos en la planificación de la educación literaria / Blanca-Ana Roig Rechou